Pyrolysis and gasification modelling of underground coal gasification and the optimisation of CO2 as a gasification agent. (1st November 2016) - Duan, Tian-Hong; Lu, Cai-Ping; Xiong, Sheng; Fu, Zhen-Bin; Chen, Ya-Zhou
Highlights: Established a two-stage reaction equilibrium method for UCG with CO2 recycling. Proposed a two-step method to find optimal parameters for UCG with CO2 recycling. CO2 is easier to lower gasifier temperature than steam of the same quantity. Gasifier temperature is the decisive factor for gasification parameters. The ratio (steam + CO2 )/O2 is important because it determines gasifiers' temperature. Abstract: In the underground coal gasification (UCG) process, a feasible method for the reduction of CO2 emissions is to capture the CO2 present in syngas and reinject it as one of the gasification agents, which is called CO2 recycling. In this process, CO2 partially replaces steam as a gasification agent, which is of particular importance in areas lacking sufficient water. To obtain a more accurate and generally applicable means of calculation, a modified equilibrium calculation method, which calculates UCG parameters in the presence of CO2 in the gasification agent over two stages and then merges the resulting data, has been established. In addition, a suitable method for establishing optimal gasification agent parameters is proposed. Corresponding MATLAB™ routines were then compiled and applied to UCG gasification agent parameters optimisation simulations using data of Ankou coal. Calculation results indicated that CO2 partially replaced steam, and that an increase in CO2 concentration in the gasification agent enhanced the reduction reaction between CO2 and hot coal. In addition, the reaction equilibrium temperature is a key factor in the process, with the temperature being influenced by the ratio of (steam + CO2 ) to O2 . Indeed, CO2 is more efficient than steam at reducing the gasifier temperature. Finally, the composition of the gasification agents was optimised by simulations using pure O2 -steam-CO2 and air-steam-CO2 mixture as the gasification agents.